Molecular profile of Epstein–Barr virus in representatives of four ethnic groups of Russia: virus types, LMP1 gene variability and malignancies - K. V. Smirnova; A. K. Lubenskaya; N. B. Senyuta; T. E. Dushenkina; V. E. Gurtsevitch (Успехи молекулярной онкологии, 2023)
Rationale. The discovery of two Epstein–Barr virus (EBV) types, EBV-1 and EBV-2, which differ in their transforming abilities stimulated their study in various populations in order to elucidate the relationship with malignant neoplasms.Aim. To study EBV-1 and EBV-2 in representatives of four ethnic groups of Russia, sequence analysis of the LMP1 oncogene in virus isolates, and search for a correlation between the types of EBV and the incidence of certain types of malignant tumors in four ethnic groups.Materials and methods. From total DNA obtained from oral washings of Adygeans, Kalmyks, Tatars and Slavs, representatives of 3 Russian republics and the Moscow region, EBV DNA was amplified; its presence and concentration were analyzed by nested PCR, and each product was examined for the virus type and LMP1 variant. Types of EBV found in representatives of In four ethnic  groups were compared with the incidence rates of malignant tumors, among which EBV-associated cases may occur, in population of three republics and the Moscow region.Results. It was observed that  higher gastric cancer and lymphomas morbidity among Tatarstan and Moscow region populations (compared to populations of Adygea and Kalmykia) correlated with predominance in these ethnic groups – Tatars and Slavs – EBV-1 type having transforming potential in vitro. In Adygeis, non-transforming EBV-2 type was prevalent, and Kalmyks were infected with both types in approximately equal proportion. however, differences between tumor morbidities between the compared groups were statistically insignificant (p >0.05). The identified spectrum of LMP1 variants, as well as the results of their sequencing, show genetic relations between EBV strains circulating in the studied ethnic groups.Conclusion. Study of EBV isolates for the first time performed in 4 ethnic groups of this country showed differences in distribution of the types of this virus but there was no correlation with tumor morbidity.